Two Distinct Heterotypic Channels Mediate Gap Junction Coupling between Astrocyte and Oligodendrocyte Connexins - Orthmann-Murphy, Jennifer L. (J Neurosci, 2007)
Genetic diseases demonstrate that the normal function of CNS myelin depends on connexin32 (Cx32) and Cx47, gap junction (GJ) proteins expressed by oligodendrocytes. GJs couple oligodendrocytes and astrocytes (O/A channels) as well as astrocytes themselves (A/A channels). Because astrocytes express different connexins (Cx30 and Cx43), O/A channels must be heterotypic, whereas A/A channels may be homotypic or heterotypic. Using electrophysiological and immunocytochemical approaches, we found that Cx47/Cx43 and Cx32/Cx30 efficiently formed functional channels, but other potential heterotypic O/A and A/A pairs did not. These results suggest that Cx30/Cx30 and Cx43/Cx43 channels mediate A/A coupling, and Cx47/Cx43 and Cx32/Cx30 channels mediate O/A coupling. Furthermore, Cx47/Cx43 and Cx32/Cx30 channels have distinct macroscopic and single-channel properties and different dye permeabilities. Finally, Cx47 mutants that cause Pelizaeus–Merzbacher-like disease do not efficiently form functional channels with Cx43, indicating that disrupted Cx47/Cx43 channels cause this disease.